Penyelidikan Sejarah tentang Masyarakat dan Budaya - Ida Zahara Adibah (Madaniyah, 2019)
Historical inquiry is one of the important activities that can contribute to the discovery and writing of history so that it can be utilized by the community. The results of this study gave birth to several theories, namely the first theory said that the composition of society is not real. The second theory says that although society is not a real compound like natural compounds, society is a synthetic compound. The third theory says that society is a real compound like other natural compounds. The fourth theory says that society is a real compound and indeed compounds with high levels of perfection.